Gradualisme Wahyu Dalam Al-Qur'an: Analisis Hikmah Nuzulul Qur'an Dan Relevansinya Terhadap Dakwah Kontemporer - A. Endang Sri Rahayu; Nasrullah Bin Sapa; Muhammad Amin Sahib (Yayasan Al-Afif, 2025)
This article discusses the meaning, process, and wisdom of Nuzulul Qur'an as a fundamental event in Islamic history with a focus on the relevance of Qur'anic gradualism to contemporary da'wah. The Qur'an, as divine revelation, was not revealed at once but gradually through the Angel Jibril to the Prophet Muhammad saw. over a period of 23 years. This study employs a qualitative method with a library research approach, analyzing both classical literature (Ulumul Qur'an) and contemporary studies. The findings show that the gradual revelation of the Qur'an carries profound wisdom: strengthening the Prophet's heart in facing challenges, providing responses to the disbelievers, facilitating memorization and comprehension, and affirming the principle of tadarruj (gradualism) in legal establishment. This research highlights that Nuzulul Qur'an is not only a spiritual event but also a divine strategy in education and da'wah that remains relevant today. The principle of Qur'anic gradualism can be integrated into modern da'wah methodologies as an effective pedagogical approach